2005
DOI: 10.1007/s00335-005-0016-0
|View full text |Cite
|
Sign up to set email alerts
|

Fine mapping of the polled locus to a 1-Mb region on bovine Chromosome 1q12

Abstract: The absence of horns in Bos taurus is under genetic control of the autosomal dominant polled locus which has been genetically mapped to the centromeric region of cattle Chromosome 1. Recently a 4-Mb BAC contig of this chromosomal region has been constructed. Toward positional cloning of the bovine polled locus, we identified 20 additional microsatellite markers spread over the contig map by random sequencing of bacterial artificial chromosome (BAC) subclones. A total of 26 markers were genotyped in 30 two-gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(41 citation statements)
references
References 12 publications
0
40
0
Order By: Relevance
“…The gene responsible for horns has not yet been characterized, but the causative mutation has been localized to a region of $1 Mbp on the proximal end of BTA1 (Brenneman et al 1996;Drögemüller et al 2005). The most recent data indicate that the polled gene lies between bp 600,000 and 1,600,000 (Drö gemü ller et al 2005). CLL 1j were therefore calculated for a subset of the four breeds with significant numbers of polled animals (i.e., Angus, Red Angus, Hereford, and Limousin).…”
Section: Permutation Testmentioning
confidence: 99%
“…The gene responsible for horns has not yet been characterized, but the causative mutation has been localized to a region of $1 Mbp on the proximal end of BTA1 (Brenneman et al 1996;Drögemüller et al 2005). The most recent data indicate that the polled gene lies between bp 600,000 and 1,600,000 (Drö gemü ller et al 2005). CLL 1j were therefore calculated for a subset of the four breeds with significant numbers of polled animals (i.e., Angus, Red Angus, Hereford, and Limousin).…”
Section: Permutation Testmentioning
confidence: 99%
“…Polledness (P) is dominant over horned (p). The gene is located at the proximal end of Bovine chromosome 1 (Brenneman et al, 1996, Drogemuller et al, 2005, Georges et al, 1993, Harlizius et al, 1997, Schmutz et al, 1995. The exact molecular nature of the polled allele remained unknown for a long time, but was recently identified as two alleles: a 202 bp insertion-deletion in most breeds, and a 260 bp haplotype in Holstein cattle.…”
Section: Introductionmentioning
confidence: 99%
“…In the past years, the position of the POLLED locus on BTA1 was refined [11,12] and candidate causal mutations were identified [2,4,5]. Recently, Medugorac et al [4] demonstrated the existence of at least two different alleles at the POLLED locus in cattle.…”
Section: Introductionmentioning
confidence: 99%